Evaluating joint destruction in rheumatoid arthritis: is it necessary to radiograph both hands and feet?. Issue 3 (12th May 2012) - Knevel, R; Kwok, KY; de Rooy, DPC; Posthumus, MD; Huizinga, TWJ; Brouwer, E; van der Helm-van Mil, AHM
Abstract : Background: Radiological damage is an important outcome measure in rheumatoid arthritis (RA), both for research and clinical purposes. Depending on the setting, both hands and feet are radiographed, or only a part of these. It is unknown whether radiographing part of the four extremities gives comparable information to radiographing both hands and feet. This study therefore aimed to compare the radiological information obtained both when evaluating single time point radiographs and progression over time, in early and advanced RA. Methods: 6261 sets of hands and feet x-rays of 2193 RA patients from Leiden, Groningen (both from The Netherlands) and North America were studied. Correlations between joint damage at different regions were compared (unilateral vs bilateral and hands vs feet). Analyses were done at single time points (cross-sectional) and for progression over time (longitudinal), both for continuous severity measures (Sharp/van der Heijde score; SHS) and binomial measures of erosiveness. Results: When studying single time points, the severity of joint damage (SHS) is highly correlated between left and right, but weakly correlated between hands and feet. Correlation coefficients were higher in advanced than early RA. These findings were comparable in the three datasets. When evaluating erosiveness using only unilateral x-rays or hands without feet, 19.3% and 24.0–40.4% are incorrectly classified as non-erosiveness. Similarly, when evaluating disease progression by imaging only unilateral x-rays or only hand x-rays, progression would have been missed in 11.6–16.2% and 21.2–31.0% of patients. Conclusion: Performing x-rays of both hands and feet yields additive information compared with imaging only a part of these.